Parosteal Osteoma of the Clavicle. (24th August 2014) - Inokuchi, Takao; Hitora, Toshiaki; Yamagami, Yosiki; Nishimura, Hideki; Yamamoto, Tetsuji
Abstract : Introduction. Osteoma is a benign, slowly growing, asymptomatic, osteogenic neoplasm. Osteoma of a bone other than the skull and facial bones is extremely rare. An extremely rare case of parosteal osteoma is reported. Case Presentation. A 51-year-old woman presented with a large mass in the left supraclavicular fossa. Radiographs and computed tomography revealed a well-defined, 9 × 6 cm, lobed mass in the midportion of the clavicle. Magnetic resonance imaging revealed that it had the same density as cortical bone. An open biopsy was performed to rule out malignant bone tumours, and parosteal osteoma was diagnosed. Four years after the biopsy, the patient was asymptomatic. Conclusion. A rare case of parosteal osteoma of the clavicle was described. Open biopsy is required to rule out a malignant bone tumour, even if parosteal osteoma is suspected based on the clinical course and imaging findings.